Effects of dietary nitrate supplementation on isometric performance and physiological responses in college bodybuilders: a randomized, double-blind, crossover study - Wang, L.; Zhao, R.; Yan, Y.; Zhang, H.; Yan, R.; Zhu, Y.; Han, Z.; Qu, Y.; Wang, R.; Li, Y.; Chao, R. ChatGPT fragen (Frontiers in Nutrition, 2025)
Introduction: In bodybuilding competitions, athletes are required to hold static poses for extended periods. This study aimed to evaluate the effects of acute beetroot juice (BJ) supplementation on isometric muscle endurance in college bodybuilding athletes.